Enhancing Patient Satisfaction - Relationship Marketing Strategies of Two Specialist Hospitals in Accra, Ghana - Afari, Augustine Adomah-; Nyamekye, Theophilus Maloreh- (International Journal of Social and Administrative Sciences, 2019)
Paying attention to the perspectives of clients, improving the competencies and skills of providers, working environment and motivating staff among others could help improve quality of care. The study examined how relationship marketing strategies enhance patient satisfaction with healthcare services. Data was gathered using a multi-stage sampling technique to recruit 200 participants to respond to a structured questionnaire at two specialist hospitals. Data was analyzed using the Statistical Package for Social Sciences / STATA software. Frequencies were run to compare the patients’ demographic variables and the relationship marketing orientation indicators. The Mann-Whitney test showed a statistically significant difference in eight relationship marketing strategies between patients of the two hospitals. The study recommends that healthcare managers integrate relationship marketing strategies into their strategic management framework so that health providers could apply them to improve upon their relationship with patients, service performance, enhance patient satisfaction and quality of care.